PARTIAL LEAST SQUARE ANALYSIS OF IMPACT OF PROMOTION ON PURCHASE INTENTION CONSUMER TRUST AS MEDIATION - Vivi Iswanti Nursyirwan (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study is to assess the impact of promotion on consumer trust, the impact of promotion on consumer purchase intentions, the impact of consumer trust on purchase intentions, and the impact of promotion on purchase intentions with consumer trust as a mediating variable. This research is a case study on Shopee e-commerce, with the research population being Shopee visitors in 2019, as many as 90.7 million. Determination of the sample by purposive as many as 100 people. This study is different from several previous studies which only examined the effect of independent variables on the dependent variable. The novelty of this research is to present a mediating variable. The approach used in data analysis using Structural Equation Modeling with Partial Least Square. The research output explains that in Shopee e-commerce there is a significant positive impact at the 10% real level for promotional variables on consumer trust, as well as promotion on purchase intention, the same results are also shown for the impact of consumer trust on purchase intention, as well as on promotional variables on purchase intention with consumer trust as a mediating variable.